Peranan Penting Internet Terhadap Peningkatan Pendapatan Gen-Z Pada Usaha Technopreneurship - Nurul Fadhillah; Muhammad Irwan Padli Nasution; Muhammad Syahbudi (Student Research Journal, 2023)
Technopreneurship is the process and creation of new businesses using technology as a basis with the hope that the creation of appropriate strategies and innovations will be able to place technology as a factor in the country's economic development. Technopreneurship is a part of entrepreneurship which involves sending a product using high technology in an innovative way to consumers to earn income from product sales/delivery. The aim of this research is to find out whether Technopreneurship has an influence on Gen-Z Income and whether Religiosity is able to moderate Technopreneurship on Gen-Z Income. The data collection method in this research is literature study and questionnaires. The research population was FEBI UIN-SU students. Sampling in this study was carried out using proportionate stratified random sampling technique. This research uses SPSS as the test. Data analysis used is validity test and reliability test, classic assumption test, hypothesis test, and moderated regression analysis (MRA). The results of the study show that Technopreneurship has an influence on Community Income, especially Gen-Z FEBI UIN-SU. Religiosity as a moderating variable is able to moderate Technopreneurship on the Income of Gen-Z FEBI UIN-SU or Religiosity is able to strengthen Technopreneurship on the Income of Gen-Z FEBI UIN-SU.